Pre-conference meeting. Gender Research Coordinators and Center Representatives - Pyburn, Rhiannon (CGIAR Collaborative Platform on Gender Research, 2017)
Presented by Rhiannon Pyburn (KIT), as part of the Gender Research Coordinators' meeting (4 December 2017), related to Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.